A EDUCAÇÃO DE FREUD E A EDUCAÇÃO EM FREUD: Um diálogo - Silva, Alessandra Lopes da (2021)
The present dissertation shows how education appears in Freud's work, therefore following the trajectory of his thinking during psychoanalytic investigation. In order to expand the psychoanalytic work beyond the clinic, this academic work raised contributions and reflections for fields of knowledge such as psychoanalysis and education. In this sense, the epistemology left by Freud provides us with the observation of his clinical practice theoretical constructs capable of understanding the uniqueness and the psychic mechanisms that guide the object choices of each subject. During the course trodden, Freudian conceptions about the constitution and functioning of the psychic system described by Freud were highlighted, elaborations that helped us to understand how education influences psychic processes and personality formation. The subject is constituted in contact with the other, this research guided us to the works in which Freud takes a look at the constitution of civilization and is attentive that to meet the civilizing purposes the subject would be condemned to renounce the instinctual desires. In this way, the author denounces the abuses of a moralizing education and the amnesia that every adult acquires and that is why he continues in the educational process, attending to narcissistic ideals in the education of children. This fact made the author yearn for a psychoanalytically oriented education. Still, we were led to understand the aggressiveness in Freud and we understand that this was interpreted by the author as necessary instincts for the subject to put himself in an active position, although later he will face the clash with the controlling forces of the superego. Finally, the impossible is presented to demonstrate Freud's disillusionment with the possibility of a total of successes when the professions mediated by the word enter the scene. However, this disillusionment is far from exhausting discussions about the approach of psychoanalysis to education, rather, it serves as food for new reflections to come.